Identifying Situational Awareness Behaviors in Trauma Teams; a Nominal Group Technique Study - Rooholamini, Azadeh; Gandomkar, Roghayeh; Basiri , Kamal; Jalili , Mohammad; Jafarian , Ali (Archives of Academic Emergency Medicine, 2022)
Introduction: Situational awareness (SA), as a nontechnical human factor, is critical to the success of a trauma team. This study aimed to identify representatives of behaviors supporting (desirable) and diminishing (undesirable) SA for trauma teams while performing the initial assessment of multi-trauma patients. Methods: This Nominal Group Technique Study was conducted on twenty attending physicians from various specialties affiliated with Tehran University of Medical Sciences, who were invited to a nominal group technique meeting in 2020. Participants were asked to write down their proposed behaviors in silence. Subsequently, each participant shared their list with the group in a round-robin format, and clarifications were made through discussion. After categorizing the ideas, we asked participants to rate each behavior’s importance on a five-point Likert scale. The consensus was defined as ≥70% agreement on a rating of 4 and 5. Results: The final SA behaviors for the trauma team consisted of 29 (22 desirable and 7 undesirable) behaviors arranged in seven dimensions: resource allocation, anticipate and plan, avoid fixation errors, call for help if needed, prioritize attention, reassess patient, and shared mental model. The most important desirable and undesirable behaviors were identified in resource allocation (n=8) and avoid fixation errors (n=7) dimensions, respectively. Resource allocation behaviors consist of ’checking necessary equipment’, ’allocating an alternative person(s) to do the required task if needed’, ’assigning tasks to the right person(s)’, and ’Addressing each team member with a requested task’. Avoid fixation errors behaviors were ’insisting on performing the procedure’, ’making decisions without considering all available information’, and ’emphasizing others’ expertise in the diagnostic process’. Conclusion: The proposed team SA behaviors may be used in assessing the trauma team performance and training program to promote trauma team SA.